Undine parte: crítica da cultura, do poder e da linguagem - Petry, Fanciele (Contingentia, 2009)
The paper aims to discuss the relations between culture, power and language in Bachmann’s story Undine geht. Undine is a water creature that lives among humans for a period of time and this fact allows her to criticize them, their way of life, of love and of relate to others. Undine’s critique is that the discourse or language shows the domination that is present in the human relations, for example, in the submission of the individual to a collectivity, as well as in the relations between men and women. She condemns this society which is regulated by money, social roles, which are false representations and generate a repression for social and individual life. This is why Undine denounces strongly the humans and their society. But she also invites the humans to know themselves and to search for the truth. Only this can liberate them from repression and give them the possibility to live a dignified life.